2010 IEEE/ACIS 9th International Conference on Computer and Information Science 2010
DOI: 10.1109/icis.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

Customer Segmentation in Mobile Carrier Choice Modeling

Abstract: Service choice behavior of customers is becoming complicated and diversified in the mobile phone market. The aim of this paper is to analyze mobile carrier choice behavior and clarify the customer segments and their decision-making factors. We classify mobile phone customers into two groups: churning customers and stable customers. Customer segmentation is carried out based on survey data for each customer group in order to clarify the decision-making factors. We propose a new service choice modeling with rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It is impossible to analyze the demand of services or products only by using customer choice-behavior models. We proposed a Framework for Scenario Simulation (FSS) to analyze market structure and estimate service demand [6], [7], [8], [9], [10], [11], [12], [13], [14], [15]. The objective of the FSS is not to obtain a demand-forecasting result but to simulate scenarios under assumed conditions according to service changes.…”
Section: Framework For Scenario Simulation (Fss)mentioning
confidence: 99%
See 4 more Smart Citations
“…It is impossible to analyze the demand of services or products only by using customer choice-behavior models. We proposed a Framework for Scenario Simulation (FSS) to analyze market structure and estimate service demand [6], [7], [8], [9], [10], [11], [12], [13], [14], [15]. The objective of the FSS is not to obtain a demand-forecasting result but to simulate scenarios under assumed conditions according to service changes.…”
Section: Framework For Scenario Simulation (Fss)mentioning
confidence: 99%
“…We have analyzed the mobile-carrier choice behavior by using the survey data conducted by the Mobile Marketing Data Laboratory in Japan to investigate the trend of mobile phone purchase behavior after the introduction of Mobile Number Portability (MNP) [10]. It is found that charge issues, phones or their functions to be used are related to the decision-making of churning customers.…”
Section: View Points Of the Surveymentioning
confidence: 99%
See 3 more Smart Citations